1999
DOI: 10.1103/physrevd.59.074013
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent analysis of the rareBdecayBXsl+

Abstract: The most general model-independent analysis of the rare B decay B→X s l ϩ l Ϫ is presented. There are ten independent local four-Fermi interactions which may contribute to this process. The branching ratio, the forward-backward asymmetry, and the double differential rate are written as functions of the Wilson coefficients of the ten operators. We also study the correlation between the branching ratio and the forwardbackward asymmetry by changing each coefficient. This procedure tells us which types of operator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 31 publications
4
92
0
Order By: Relevance
“…The decay amplitude for the b → sℓ + ℓ − transition in a general model independent form can be written in the following way (see [21], [25,26])…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The decay amplitude for the b → sℓ + ℓ − transition in a general model independent form can be written in the following way (see [21], [25,26])…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In general, new physics effects manifest themselves in rare decays either through new contributions to the Wilson coefficients existing in the SM or by introducing new structures in the effective Hamiltonian which are absent in the SM (see for example [21], [25]- [27] and the references therein). At this point we would like to remind that, the sensitivity of the physical observables to the new physics effects in the "heavy pseudoscalar meson → light pseudoscalar (vector) meson" transitions, like B → K(K * )ℓ + ℓ − are studied systematically in [21,27,28], using the most general form of the effective Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…The decay b → sℓ + ℓ − suffers from severe backgrounds of J/ψ and ψ ′ resonance contributions in the measurement of branching fraction, and so it may not be easy to uncover new physics cleanly [3]. However, a number of methods have been discussed to detect new physics through the details of the decay process, such as differential distributions or polarization effects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this observable would provide a direct measurement of the physics of scalar and pseudoscalar type interactions. We also note that more information about these new interactions can be obtained by combining the present analysis with the other observables from B → X q ℓ + ℓ − [18].…”
mentioning
confidence: 94%